The effect of alternative feed on the growth of Bombyx mori L. in Renggeang Village, Polewali Mandar Regency, West Sulawesi, Indonesia: Pengaruh pakan alternatif terhadap pertumbuhan Bombyx mori L. di Desa Renggeang, Kecamatan Polewali Mandar, Sulawesi Barat, Indonesia - Nurdin, Muhammad Rizaldi Trias Jaya Putra; Hasan, Phika Ainnadya; Putera, Alexander Kurniawan Sariyanto; Isdaryanti; Rahman, Sari Rahayu; Nursyamsi SY (Jurnal Entomologi Indonesia, 2025)
Mulberry (Morus sp.) is the primary feed for silkworms (Bombyx mori L.) and determines cocoon quality. However, limited land availability and seasonal changes pose challenges for a consistent mulberry leaf supply, prompting research into alternative feeds. This study aimed to evaluate the effects of alternative feeds on the growth of B. mori, including the length and width of silkworms, the number of live and dead silkworms, and the feed consumption of silkworms. A total of 500 silkworms were divided into six treatments with three replicates each. The treatments were mulberry leaves (K), castor leaves (P1), cassava leaves (P2), broiler chicken feed (P3), castor and mulberry leaves combination (P4), cassava and mulberry leaves combination (P5), broiler chicken feed and mulberry leaves combination (P6). Combined feeds were given at a 1:1 ratio. The results confirmed that B. mori exclusively feeds on mulberry leaves, as no silkworms survived  on P1, P2, or P3 treatments. All combination feed treatments (P4, P5, P6) showed that silkworm growth results were not significantly different from the control treatment (K). Therefore, we recommend using all combination feeds as an alternative feed in B. mori cultivation. However, the best combination feed treatment was shown by P6 with the highest silkworm length and width (3.69 cm; 0.57 cm) and the highest feed consumption (44.16 grams), and P5 with the highest percentage of survival rate (75%) and the lowest percentage of death rate (25%).